SOCIO-ECONOMIC AND MEDICINAL IMPORTANCE OF EUCALYPTUS TREES: A CRITICAL REVIEW - Oke , R.A.; Adetola , O.O.; Owoeye , Y.T.; Akemien , N.N.; Adaaja , B.O.; Bakpolor , V.R.; Murtala , M.O. (Global Prosperity, 2021)
Pollution is a great issue of the environment that is gaining global attention currently because industrial development has disturbed the ecosystem of the world and depleting the ozone. It has resulted in global warming and increased the temperature, which has changed the climate at different levels globally. According to a world report, about 25% of forest land is required for ecosystem favourability. There are so many trees which are grown in the world. Among these trees, Eucalyptus is very popular and was first grown in Australia. This plant has both economic and health benefits. Pharmacologists converted this plant into medicine for different health disease control in the world. Essential Oil squeezed from the leaf and bark of the tree and leaves also possess great benefits. The well-known diseases are blood pressure, diabetes, Arthritis, plague, Cough etc., while it is also used for mosquitoes, termites, and white ants control. The plant also has its disadvantage; it decreases the water table and disturbs the tube well system. Those plants need much water, so they compete with other plants in the area and affect the size of the plant. The major objective was to review the socio-economic and medicinal value of the eucalyptus tree. Total 19 articles were downloaded from the net and reviewed in depth. The result indicates that the Eucalyptus tree has many socio-economic and medicinal values